2000
DOI: 10.1029/2000wr900105
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic processes and peak discharge response to forest removal, regrowth, and roads in 10 small experimental basins, Western Cascades, Oregon

Abstract: Abstract. The magnitude, seasonality, and duration of peak discharge responses to forest removal and regrowth and roads in 10 pairs of experimental basins in the western Cascade Range of Oregon are consistent with fundamental water balance and routing concepts in hydrology. Hypothesized effects of forestry treatments on evapotranspiration, cloud water interception, snowpack dynamics, and subsurface flow interception vary predictably by season, geographic setting, amount of forest canopy removal, stage of canop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
151
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 39 publications
4
151
0
6
Order By: Relevance
“…Relevant publications include Lall (2005), Pittock (2002), Trenberth (1999), Benestad (2003), Beniston et al (1997), Hanson et al (2004), Svensson et al (2005), Hisdal et al (2001), and Llasat et al (2005). Similarly, there have been numerous publications on land cover change effects on floods, low flows and, more generally water yield, including Robinson et al (2003), Brown et al (2005), Andréassian (2004), Cosandey et al (2005), Bonell and Bruijnzeel (2005), Bonell (1999), Mahé et al (2005b), Archer (2003), Jones (2000), Bronstert et al (2002) and Pfister et al (2004). Rodriguez-Iturbe (2000), Peterson et al (2000), Woods (2005) and Anderson et al (2005) provide perspective on hydrological variability and other background information highly relevant to the issue of scales of climate variability and land cover change impact on flooding and low flows.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant publications include Lall (2005), Pittock (2002), Trenberth (1999), Benestad (2003), Beniston et al (1997), Hanson et al (2004), Svensson et al (2005), Hisdal et al (2001), and Llasat et al (2005). Similarly, there have been numerous publications on land cover change effects on floods, low flows and, more generally water yield, including Robinson et al (2003), Brown et al (2005), Andréassian (2004), Cosandey et al (2005), Bonell and Bruijnzeel (2005), Bonell (1999), Mahé et al (2005b), Archer (2003), Jones (2000), Bronstert et al (2002) and Pfister et al (2004). Rodriguez-Iturbe (2000), Peterson et al (2000), Woods (2005) and Anderson et al (2005) provide perspective on hydrological variability and other background information highly relevant to the issue of scales of climate variability and land cover change impact on flooding and low flows.…”
Section: Introductionmentioning
confidence: 99%
“…HJA is also the location for much of the analysis from Jones & Grant (1996) and the papers that followed (Beschta et al, 2000;Jones & Grant, 2001;Thomas & Megahan, 1998;2001) debating the interpretation of results of statistical analyses of paired-catchment data. Detailed site descriptions of the overall HJA and the small basins can be found in Rothacher et al (1967), Jones & Grant (1996) and Jones (2000). Our study focuses on the small catchments WS1 (treatment, 0.96 km For each catchment a series of runoff peaks was derived.…”
Section: Study Catchmentsmentioning
confidence: 99%
“…Areas that have been logged show less evapotranspiration because of the loss of vegetation and greater overland flow because of soil compaction, both of which lead to higher peak, seasonal, and annual flows from a catchment (Harr et al 1979). Jones (2000) folUld that this effect on peak flows may diminish considerably and possible reverse itself as regrowth occurs.…”
mentioning
confidence: 99%
“…Research has shown that the logging of the forests of western Oregon increase runoff, at least initially (Harr et al 1979;Jones 2000). Areas that have been logged show less evapotranspiration because of the loss of vegetation and greater overland flow because of soil compaction, both of which lead to higher peak, seasonal, and annual flows from a catchment (Harr et al 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation